Exchange Rate Pass-Through into Japanese Import Prices: Evidence at Both Bilateral and Product Levels - Channary Khun (Pompea College of Business, 2021)
This study investigates the degree of the exchange rate pass-through to Japanese bilateral import prices at the product level for major Japan's trading partners (US, EU, and Asian NIEs) for a period (1998:1-2010:12) dubbed as Japan's lost decade and marked by a gradual the exchange rate appreciation against the US dollar. By considering both country and product dimensions in a unified framework, this study makes one of the first attempts to analyze the responsiveness of Japanese import prices to exchange rate movement. The empirical analysis suggests a declining exchange rate pass-through to Japanese import prices at the bilateral level in some product categories but increasing in others. However, we find no evidence of the changes in exchange rate pass-through for manufacturing, machinery, and overall product level for each of these partners. Our finding sheds light on the recent decline in exchange rate pass-through to Japanese multilateral import prices and helps calibrate its trade relationship with its partner countries.